The impact of synthetic method on the catalytic application of intermetallic nanoparticles. Issue 36 (3rd September 2020) - Williams, Benjamin P.; Qi, Zhiyuan; Huang, Wenyu; Tsung, Chia-Kuang
Abstract : This review seeks to connect the synthetic method and catalytic application of intermetallic nanoparticles to guide their future development. Abstract : Intermetallic alloy nanocrystals have emerged as a promising next generation of nanocatalyst, largely due to their promise of surface tunability. Atomic control of the geometric and electronic structure of the nanoparticle surface offers a precise command of the catalytic surface, with the potential for creating homogeneous active sites that extend over the entire nanoparticle. Realizing this promise, however, has been limited by synthetic difficulties, imparted by differences in parent metal crystal structure, reduction potential, and atomic size. Further, little attention has been paid to the impact of synthetic method on catalytic application. In this review, we seek to connect the two, organizing the current synthesis methods and catalytic scope of intermetallic nanoparticles and suggesting areas where more work is needed. Such analysis should help to guide future intermetallic nanoparticle development, with the ultimate goal of generating precisely controlled nanocatalysts tailored to catalysis.